Association of Veterinary Hematology and Transfusion Medicine (AVHTM) Transfusion Reaction Small Animal Consensus Statement (TRACS) Part 2: Prevention and monitoring. Issue 2 (10th March 2021) - Davidow, Elizabeth B.; Blois, Shauna L.; Goy‐Thollot, Isabelle; Harris, Lauren; Humm, Karen; Musulin, Sarah; Nash, Katherine J.; Odunayo, Adesola; Sharp, Claire R.; Spada, Eva; Thomason, John; Walton, Jenny; et al.
Abstract: Objective: To systematically review available evidence to develop guidelines for the prevention of transfusion reactions and monitoring of transfusion administration in dogs and cats. Design: Evidence evaluation of the literature (identified through Medline searches through Pubmed and Google Scholar searches) was carried out for identified transfusion reaction types in dogs and cats. Evidence was evaluated using PICO (Population, Intervention, Comparison, Outcome) questions generated for each reaction type. Evidence was categorized by level of evidence (LOE) and quality (Good, Fair, or Poor). Guidelines for prevention and monitoring were generated based on the synthesis of the evidence. Consensus on the final recommendations and a proposed transfusion administration monitoring form was achieved through Delphi‐style surveys. Draft recommendations and the monitoring form were made available through veterinary specialty listservs and comments were incorporated. Results: Twenty‐nine guidelines and a transfusion administration monitoring form were formulated from the evidence review with a high degree of consensus Conclusions: This systematic evidence evaluation process yielded recommended prevention and monitoring guidelines and a proposed transfusion administration form. However, significant knowledge gaps were identified, demonstrating the need for additional research in veterinary transfusion medicine.